EUROCOURSE recipe for cancer surveillance by visible population-based cancer RegisTrees® in Europe: From roots to fruits. Issue 9 (June 2015) - Coebergh, Jan Willem; van den Hurk, Corina; Louwman, Marieke; Comber, Harry; Rosso, Stefano; Zanetti, Roberto; Sacchetto, Lidia; Storm, Hans; van Veen, Evert-Ben; Siesling, Sabine; van den Eijnden-van Raaij, Janny
Abstract Currently about 160 population-based cancer registries (CRs) in Europe have extensive experience in generating valid information on variation in cancer risk and survival with time and place. Most CRs cover all cancers, but some are confined to specific cancers or to children. They cover 15–55% of the populations in all of the larger member states of the European Union (EU), except the United Kingdom (UK), and 100% coverage in 80% of those with populations below 20 million. The EU FP 7 EUROCOURSE project, which operated in 2009–2013, explored the essential role of CRs in cancer research and public health, and also focused attention on their programme owners (POs) and stakeholders (e.g. cancer societies, oncological professionals, cancer patient groups, and planners, providers and evaluators of cancer care and mass screening). Generally, all CRs depended on their regional and/or national oncological context and were increasingly involved in population-based studies of quality of cancer care, long-term prognosis and quality of life, one third being very active. Within the public health domain, CRs, in addition to describing the variety of environmental and lifestyle-related cancer epidemics, have also contributed actively to aetiologic research by a European databases that showed wide discrepancies in cancer risk and survival across the EU, and in more depth by follow-up of cohorts and recruitment for case-control studies. CRs were also actively contributing to independent evaluation of mass screening as an intervention which affects quality of care and cancer mortality. The potential of CRs for clinical evaluation has grown substantially through interaction with clinical stakeholders and more incidentally biobanks, also with greater involvement of patient groups – with a special focus on elderly patients who generally do not take part in clinical trials. Whereas 25–35% of CRs are active in a range of cancer research areas, the rest have a low profile and usually provide only incidence and survival data. If they are unable to do so because POs and stakeholders do not demand it, they might also be inhibited by data protection restrictions, especially in German and French speaking countries. The value of population-based studies of quality of oncologic care and mass screening and the flawless reputation with regard to data protection of intensively used CRs in the northwest of Europe offered a sharp contrast, although they also follow the 1995 EU guideline on data protection. CRs thus offer a perfect example of what can be done with sensitive and minimal data, also when enriched by linkages to other databases. Intensive use of the data has allowed CR research departments to take on a visible expertise-based profile but a neutral in many public controversies in preventive oncology. Their management and fundability also appeared to benefit from externally classifying the wide array of tumour- or tract-specific intelligence and research activities for the various users in oncology and public health and also patients – who are the source of the data – are better informed. Transparency on what CRs enable may also improve through programmes of research have been deemed essential to our funding POs (ministries, cancer charities, cancer centres or public health institutes) who might benefit from some guidance to – often suboptimal –governance. Therefore, a metaphoric RegisTree® has been developed for self-assessment and to clarify CR working methods and domain-specific performance to stakeholders and funding agencies, showing much room for development in many CRs. All in all, CRs are likely to remain unique sources of independent expert information on the burden of cancer, indispensable for cancer surveillance, with increased attention to cancer survivors, up to 4% of the population. Investments in the expanding CR network across Europe offer an excellent way forward for comparative future cancer surveillance with so many epidemiologic and clinical changes ahead.